Teacher Career Development Management At Primary School - Sherly Carolline Santo; Budi Purwoko; Andi Kristanto; Mohammad Syahidul Haq; Amrozi Khamidi; Mochamad Nursalim (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2026)
This study aims to analyze teacher career development management at SDS Aqil Global Islamic School and SDS Educate Center Mas in Batam City. The research employed a descriptive qualitative approach with a multisite case study design through interviews, observations, and documentation. The research participants consisted of principals, vice principals, senior teachers, new teachers, and foundation representatives. Data analysis was conducted interactively through data reduction, data presentation, and conclusion drawing. The findings revealed that teacher career development was implemented through three main stages: planning, implementation, and evaluation. In the planning stage, schools systematically conducted needs analysis and teacher competency mapping. The implementation stage was carried out through training, workshops, mentoring, learning communities, and additional assignments to improve teacher professionalism. The evaluation stage involved supervision, performance appraisal, and continuous feedback. The results also showed that principals’ support played a significant role in enhancing teachers’ competence, motivation, collaboration, and learning quality. Structured career development programs were proven to improve educational quality, strengthen learning culture, and sustain teacher professionalism in primary schools. This study recommends strengthening needs-based career development programs, improving supporting facilities, and conducting continuous evaluation so that teachers’ competencies can develop optimally in line with educational and technological advancements to support innovative, adaptive, and sustainable learning quality nationally.